2014
DOI: 10.1165/rcmb.2013-0515oc
|View full text |Cite
|
Sign up to set email alerts
|

Ozone Induces a Proinflammatory Response in Primary Human Bronchial Epithelial Cells through Mitogen-Activated Protein Kinase Activation Without Nuclear Factor-κB Activation

Abstract: Ground-level ozone (O3) is a ubiquitous environmental air pollutant that is a potent inducer of airway inflammation and has been linked with respiratory and cardiovascular morbidity and mortality. Some studies using transformed or immortalized cells have attributed O3-mediated expression of inflammatory cytokines with activation of the canonical NF-κB pathway. In this study, we sought to characterize the O3-mediated activation of cellular signaling pathways using primary human bronchial epithelial cells obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 37 publications
3
34
1
Order By: Relevance
“…This is in contrast to other studies which have shown O 3 -induced cytokine responses in differentiated NHBE cells at O 3 concentrations comparable to what was used in this study (Ahmad et al, 2011, Damera et al, 2009, McCullough et al, 2014). It is important to note that in these other studies the amount of time the NHBE cells were maintained at ALI conditions to differentiate prior to exposure varied from a couple of days to 2 weeks.…”
Section: Discussioncontrasting
confidence: 99%
“…This is in contrast to other studies which have shown O 3 -induced cytokine responses in differentiated NHBE cells at O 3 concentrations comparable to what was used in this study (Ahmad et al, 2011, Damera et al, 2009, McCullough et al, 2014). It is important to note that in these other studies the amount of time the NHBE cells were maintained at ALI conditions to differentiate prior to exposure varied from a couple of days to 2 weeks.…”
Section: Discussioncontrasting
confidence: 99%
“…Based on our findings, it can be speculated that MAPK signaling has a more prominent role in CS-induced airway epithelial inflammatory responses than NF-κB. This is further supported by findings from a recent study examining ozone-induced proinflammatory responses by differentiated airway epithelial cells, revealing the MAPKdependent and NF-κB-independent induction of inflammatory mediators [53] .…”
Section: Discussionsupporting
confidence: 87%
“…Pollutants, such as ozone, 74 nitrogen oxide, 75 and particular matter <2.5 mm in diameter, 76 can induce airway hyperresponsiveness and neutrophilic airway inflammation; however, the mechanism is unknown. Probable air pollutants cause oxidative injury to the airways, which leads to inflammation, remodeling, and increased risk of sensitization.…”
Section: Air Pollutioneinduced Asthmamentioning
confidence: 99%